Resource utilization and cost of influenza requiring hospitalization in Canadian adults: A study from the serious outcomes surveillance network of the Canadian Immunization Research Network. Issue 2 (24th January 2018) - Ng, Carita; Ye, Lingyun; Noorduyn, Stephen G; Hux, Margaret; Thommes, Edward; Goeree, Ron; Ambrose, Ardith; Andrew, Melissa K.; Hatchette, Todd; Boivin, Guy; Bowie, William; ElSherif, May; et al.
Abstract : Background: Consideration of cost determinants is crucial to inform delivery of public vaccination programs. Objectives: To estimate the average total cost of laboratory‐confirmed influenza requiring hospitalization in Canadians prior to, during, and 30 days following discharge. To analyze effects of patient/disease characteristics, treatment, and regional differences in costs. Methods: Study utilized previously recorded clinical characteristics, resource use, and outcomes of laboratory‐confirmed influenza patients admitted to hospitals in the Serious Outcomes Surveillance (SOS), Canadian Immunization Research Network (CIRN), from 2010/11 to 2012/13. Unit costs including hospital overheads were linked to inpatient/outpatient resource utilization before and after admissions. Results: Dataset included 2943 adult admissions to 17 SOS Network hospitals and 24 Toronto Invasive Bacterial Disease Network hospitals. Mean age was 69.5 years. Average hospital stay was 10.8 days (95% CI: 10.3, 11.3), general ward stays were 9.4 days (95% CI: 9.0, 9.8), and ICU stays were 9.8 days (95% CI: 8.6, 11.1) for the 14% of patients admitted to the ICU. Average cost per case was $14 612 CAD (95% CI: $13 852, $15 372) including $133 (95% CI: $116, $150) for medical care prior to admission, $14 031 (95% CI: $13 295, $14 768) during initial hospital stay, $447 (95% CI: $271, $624) post‐discharge, including readmission within 30 days. Conclusion: The cost of laboratory‐confirmed influenza was higher than previous estimates, driven mostly by length of stay and analyzing only laboratory‐confirmed influenza cases. The true per‐patient cost of influenza‐related hospitalization has been underestimated, and prevention programs should be evaluated in this context.